1999
DOI: 10.1055/s-1999-14025
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of the Essential Oil of Croton nepetaefolius in Rats: Role of the Autonomic Nervous System

Abstract: Cardiovascular effects of intravenous (i.v.) treatment with the essential oil of Croton nepetaefolius (EOCN) were investigated in rats. Additionally, this study examined the importance of the autonomic nervous system in mediation of the EOCN-induced changes in mean aortic pressure (MAP) and heart rate (HR). In both pentobarbitone-anaesthetised and conscious rats, i.v. bolus injections of EOCN (1 to 50 mg/kg) elicited dose-dependent decreases in MAP and HR. Both decreases were of the same order of magnitude or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
55
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 0 publications
13
55
0
2
Order By: Relevance
“…Baseline MAP and HR values of anesthetized or conscious, freely moving, normotensive rats were of the same order of magnitude as those previously reported using the same preparation (Lahlou et al 1999(Lahlou et al , 2001). In both groups, i.v.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Baseline MAP and HR values of anesthetized or conscious, freely moving, normotensive rats were of the same order of magnitude as those previously reported using the same preparation (Lahlou et al 1999(Lahlou et al , 2001). In both groups, i.v.…”
Section: Discussionsupporting
confidence: 83%
“…These findings with i.v. hexamethonium are in line with those previously reported in normotensive rats treated with EOCN (Lahlou et al 1999) and suggest that the hypotensive response to 1,8-cineole may be due to an active vascular relaxation rather than to a withdrawal of sympathetic tone. Such a hypothesis is corroborated by the present finding that in rat isolated aorta preparations, 1,8-cineole was able to inhibit the potassiuminduced contraction in a concentration-dependent manner.…”
Section: Figsupporting
confidence: 90%
See 2 more Smart Citations
“…Available studies have dealt only with the chemical composition of the essential oil of C. nepetaefolius (EOCn) and its pharmacological effects on intestinal, respiratory and vascular smooth muscle and on arterial pressure (2)(3)(4)(5)(6). While EOCn is present in relatively large quantities in the leaves of the plant (1% yield) (7), pharmacological investigations have shown that it has potent antispasmodic activity, consistent with its use in folk medicine.…”
mentioning
confidence: 99%